2017
DOI: 10.1159/000448069
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Squamous Cell Carcinoma

Abstract: Pancreatic squamous cell carcinoma (SCC) is a rare event. Here, we present a 56-year-old man with pancreatic SCC. Imaging methods demonstrated a hypodense mass at the head and trunk of the pancreas. Also, some lymphadenopathy has been seen around the pancreas and para-aorta. The mass created pressure and encasement on the celiac trunk, portal vein, and arteries of the liver and spleen. Endoscopic ultrasound showed a mass lesion of 45–37 mm (mixed echoic) at the trunk of the pancreas. Histological examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…As the normal pancreatic tissues does not include squamous epithelium, it is still unclear the histogenesis of primary tumors with squamous component [4,5,6,12]. It was even postulated the origin in a pluripotent primitive-or remnant aberrant squamous cell from embryonal period [1,[4][5][6][7]11,[13][14][15], or, based on other authors, it is rather about a collision tumor than a really pure SCC, in which the tumor stem cells from glandular part might be dedifferentiated in cells with squamous arhitecture [1,6,7,11]. On the other hand, as most of the pancreatic cancers occur on the background of chronic pancreatitis, metaplastic transformation can be the precursor lesion [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the normal pancreatic tissues does not include squamous epithelium, it is still unclear the histogenesis of primary tumors with squamous component [4,5,6,12]. It was even postulated the origin in a pluripotent primitive-or remnant aberrant squamous cell from embryonal period [1,[4][5][6][7]11,[13][14][15], or, based on other authors, it is rather about a collision tumor than a really pure SCC, in which the tumor stem cells from glandular part might be dedifferentiated in cells with squamous arhitecture [1,6,7,11]. On the other hand, as most of the pancreatic cancers occur on the background of chronic pancreatitis, metaplastic transformation can be the precursor lesion [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…It was even postulated the origin in a pluripotent primitive-or remnant aberrant squamous cell from embryonal period [1,[4][5][6][7]11,[13][14][15], or, based on other authors, it is rather about a collision tumor than a really pure SCC, in which the tumor stem cells from glandular part might be dedifferentiated in cells with squamous arhitecture [1,6,7,11]. On the other hand, as most of the pancreatic cancers occur on the background of chronic pancreatitis, metaplastic transformation can be the precursor lesion [1,[4][5][6][7]. As in our second case the immunoprofile was similar in both glandular and squamous component we tend to believe that like adeno-neuroendocrine tumors (MANEC), adeno-squamous and SCC of the pancreas have the same origin in a Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 206 pancreas autopsy specimens from patients with no known history of cancer, Mukada et al reported squamous metaplasia in 16.4% of cases . It is unclear how primary SCC develops in an organ histologically devoid of native squamous cells; theories include development from a progenitor cell, malignant transformation of inflammatory‐induced squamous metaplasia (possibly related to chronic pancreatitis or pancreatic stent placement), and squamous transformation of AC . (Figure ) Others hypothesize that primary SCC of the pancreas is, in fact, metastatic SCC arising in an occult primary elsewhere in the body …”
Section: Introductionmentioning
confidence: 99%